Characterization and properties of Sb-doped BaTi O3 powders - Tangjuank S. (2014)
Improved single-phase nanocrystalline BaTi O3 powders may be prepared at 700 °C by the sol-gel acetate process to which 1-3 wt % Sb is added as dopant. Following calcination at 1200 °C, the resulting average particle size as determined by scanning electron microscopy analysis is in the range of 50-150 nm. The dielectric results show that fired samples containing 1 wt % Sb have the highest relative permittivity, with εr ≈4500 and TC =52 °C, whereas undoped samples have εr ≈3300 and TC =120 °C. © 2007 American Institute of Physics.